A NOTE ON MAPPINGS AND ALMOST MENGER AND RELATED SPACES - Kočinac, Ljubiša (Bulletin of Natural Sciences Research, 2016)
We consider behaviour of the almost Menger, almost Rothberger, almost Hurewicz, and almost gamma-set properties under several kinds of mappings between topological spaces.